Phonotactic Divergence and Consonant Cluster Adaptation in Javanese and English: A Contrastive Analysis - Ayuningtyas , Diah Ikawati (Indonesian Scientific Publication, 2024)
This study presents a contrastive phonological analysis of consonant cluster patterns in Javanese and English. The primary objective is to examine structural phonotactic constraints, particularly cluster types, sonority sequencing, and repair strategies, with a focus on cross linguistic and bilingual contexts. Employing corpus based data and phonological inventories, the analysis identifies cluster combinations in both onset and coda positions, and evaluates conformity to the Sonority Sequencing Principle (SSP). Javanese displays a preference for simple, sonority conforming onset clustersprimarily C+r/l and s+r,wand rarely produces complex codas or CCC onsets outside of loanwords. English, by contrast, permits a wide array of clusters, including frequent SSP violating s+stop+liquid sequences and up to four consonant codas. These typological differences are reflected in structural adaptations: Javanese and Indonesian speakers regularly apply vowel epenthesis to repair illegal clusters in both loanwords and interlanguage forms (e.g., /stress/ → /setres/, /spring/ → /sepering/). Dialectal variation within Javanese and cognitive control in bilinguals further shape these outcomes. The results affirm that Javanese conforms more strictly to SSP and syllable templates, whereas English tolerates greater phonotactic flexibility. Repair strategies like epenthesis, simplification, and truncation highlight the interface between native phonological constraints and second language adaptation. These findings contribute to phonotactic theory, bilingual phonology, and L2 instruction by clarifying how learners accommodate foreign cluster structures.